Study on natural breeding sites of sand flies (Diptera: Phlebotominae) in areas of Leishmania transmission in Colombia (2015)
ABSTRACT: Background: The location of the microhabitats where immature phlebotomine sand flies of the genus Lutzomyia develop is one of the least-known aspects of this group of medically important insects. For this reason strategies of source reduction approach for their control have not been possible in contrast to other insect vectors (such as mosquitoes), because their juvenile stages in terrestrial microhabitats is difficult to detect. Methods: Direct examination of soil samples, incubation of substrates and the use of emergence traps were the methods used to identify juvenile stages in 160 soil samples from urban and forest habitats within the foci of Leishmania transmission in Colombia. Immatures collected were identified subsequent from the rearing and emergence of adults using taxonomic keys or the analysis of the mitochondrial marker cytochrome oxidase I. Plant species associated with the natural breeding sites were identified and physicochemical properties of the soils were analyzed. Results: A total of 38 (23.7%) sampling sites were identified as breeding sites, 142 phlebotomine sand flies were identified, belonging to 13 species of the genus Lutzomyia and two of Brumptomyia. The greatest numbers of immature were found within the tabular roots (51 immature sand flies from eight positive sites) and bases of trees (35 immature sand flies from 11 sites). The characterization and presence of the tree species (mainly Ceiba pentadra, Anacardium excelsum, Pseudosamanea guachapale) and the physicochemical properties (relative humidity and carbon/nitrogen ratio) of the soils associated with these breeding sites are significant factors in explaining the diversity and abundance of phlebotomine sand flies. Conclusions: Immature phlebotomine sand flies of the genus Lutzomyia in Colombia can be found in a wide variety of breeding sites rich in organic matter, high relative humidity and are associated with a typical vegetation of each locality. These results provide new perspectives for the study of the ecology of the genus Lutzomyia in Colombia and the development of vector control strategies.